Methods, Theoretical Frameworks and Hope for Knowledge Organization - Martinez-Avila, Daniel [UNESP]; Beak, Jihee (Ergon-verlag, 2016)
This paper analyzes the epistemic stances and research methods and techniques of the thirty-three journal articles that Hope Olson published during the period 1991-2015. For the analysis of the epistemic stances, we use Hjorland's classification of epistemological stances (namely rationalism, empiricism, historicism, and pragmatism), and for the classification of methodologies and methods we use the taxonomy used by Beak et al., loosely based on the consulted literature. Results of the analysis are presented and discussed in the context of the poststructuralist stance adopted by Hope Olson throughout her career. We highlight the impact of the innovative research methods and techniques and poststructuralist theoretical frameworks that Hope Olson introduced and used in knowledge organization.
Keywords: Hope Olson; knowledge organization; methods; methodologies; epistemology; classification